Thermoelectric properties tuning in mixed valence inorganic solid compound - In5S5Br by oriented mutual chalcogenide substitutions. (January 2021) - Xhaxhiu, Kledi; Korpa, Arjan; Andoni, Adelaida; Kvarnström, Carita; Damlin, Pia; Bente, Klaus
Graphical abstract: Highlights: In5 Ch5 Br (Ch = S, Se) contain indium simultaneously in three different oxidation states. Bulk sample of In5 S5 Br shows p -type conductivity which shifts to n-type conductivity upon mutual S-Se substitution. The Seebeck potential changes (decreases/increases) linearly with the temperature difference increase. Single crystal electrical conductivity increases with the increase of the selenium content in the structure. DTA and HT-powder XRD data show incongruent melting to binary compounds. Abstract: The mixed-valence compounds In5 S5 Br, In5 S3 Se2 Br, In5 SSe4 Br, and In5 Se5 Br reveal interesting thermoelectric properties. As the selenium content in the structure of In5 S5 Br increases, the Seebeck potential increases. In5 S5 Br exhibits low Seebeck potentials within the studied range (ΔT = 0–80 K) and a maximum value of 0.34 mV for ΔT = 80 K. It behaves as a p -type semiconductor. The substitution of two sulphur species by selenium, as in In5 S3 Se2 Br, shows n -type conductivity and approx.−16.00 mV for the same ΔT. Further substitutions of sulphur in the structure maintain the n -type conductivity and increase dramatically the Seebeck potential to -225.26 mV (ΔT = 80 K). Repeating cycles of Seebeck potential variation over time for In5 Se5 Br and In5 SSe4 Br, show differences in their potentials, shape of maxima as well as in their recovery time. Electrical conductivities from 0.3 pS for In5 S5 Br up to 13 pS for In5 Se5 Br, strongly influence their thermoelectricity.